Teacher’s pedagogical competencies on the vocational high school of Padang City - Nellitawati Nellitawati (Jurnal Konseling dan Pendidikan, 2019)
Teachers are an important part of education, the results of the achievements of education are proportional to the competencies of the teacher. One of the competency that teachers must have is pedagogical competence. This study aims to describe how the teacher’s pedagogical competencies on vocational high school of Padang City, with 86 research subjects, using the Teacher’s Pedagogical Competencies Inventory. The results of the study revealed that the teacher’s pedagogical competencies on vocational high school of Padang City is in a good category and this needs to be maintained and should be improved further.